1995
DOI: 10.3109/00365529509096311
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Long-Chain Alkanoylcholines in Rat Intestinal Loops

Abstract: The long-chain alkanoylcholines were rapidly hydrolyzed. The rates of the reaction and the chain-length dependence were similar to those reported earlier in vitro. At high substrate concentrations the hydrolysis reaction was inhibited. This could be due to conformational changes of the enzyme, caused by the adsorption of the cationic amphiphile, or to a decrease in the free substrate concentration after incorporation of the amphiphilic ester into the lipid layer of the cell membranes. The enzymatic activity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Apart from these enzymes, more specific serine proteases such as trypsin cleaving proteins at the carboxyl side of the amino acids lysine or arginine, as well as the butyrylcholinesterase (BChE) are involved in the degradation of cationic and ionizable cationic lipids. [ 6a,40 ] The degradation by trypsin has recently been exploited for ionizable cationic lipids based on the amino acids lysine and arginine. [ 5d,6a,40c,41 ] Furthermore, cell membrane bound enzymes seem to contribute to the degradation of biodegradable lipids.…”
Section: Biodegradationmentioning
confidence: 99%
“…Apart from these enzymes, more specific serine proteases such as trypsin cleaving proteins at the carboxyl side of the amino acids lysine or arginine, as well as the butyrylcholinesterase (BChE) are involved in the degradation of cationic and ionizable cationic lipids. [ 6a,40 ] The degradation by trypsin has recently been exploited for ionizable cationic lipids based on the amino acids lysine and arginine. [ 5d,6a,40c,41 ] Furthermore, cell membrane bound enzymes seem to contribute to the degradation of biodegradable lipids.…”
Section: Biodegradationmentioning
confidence: 99%
“…The in vitro hydrolysis studies were complemented with an investigation on the hydrolysis of alkanoylcholines in a biological environment, the rat intestine (5). These studies showed that alkanoylcholines are readily hydrolyzed in vivo and that the rate of hydrolysis decreases with increasing hydrocarbon chain length.…”
mentioning
confidence: 99%
“…Hydrolysis of myristoylcholine by neuromuscular junction BChE is inhibited by the dual acetylcholinesterase/butyrylcholinesterase inhibitor eserine (also known as physostigmine), but with even greater sensitivity than that of acetylcholine . The hydrolysis of multiple long-chain acylcholines species by horse serum BChE has been established. , The eserine-inhibitable hydrolysis of succinylcholine esters and other dicarboxylic acid-choline esters confirms the importance of BChE in inactivating muscle relaxants like succinylcholine …”
Section: Metabolism Of Acylcholinesmentioning
confidence: 85%
“…While the biology of acylcholines is beginning to be understood, aspects of their metabolism and biochemistry have been described. BChE shows hydrolytic activity toward long-chain acylcholines, ,, which might serve to control systemic acylcholine levels (explaining class-level trends observed with disease). Additional evidence can also be observed in the negative correlation between acylcholine levels and BChE activity, which mirrors that of another known substrate of BChE, acyl-ghrelin. , …”
Section: Omic Analyses Expand Endogenous Targets For Bchementioning
confidence: 99%
See 1 more Smart Citation